The measurement of information integrity - Seadle, Michael S. 1950- (Abingdon, Oxon New York, NY Routledge, 2022)
Arguing that there never was a time when politicians did not prevaricate and when some communities did not doubt conclusions that others considered to be facts, The Measurement of Information Integrity puts the post-truth era in context and offers measures for integrity in the modern world. Incorporating international examples from a range of disciplines, this book provides the reader with tools that will help them to evaluate public statements - especially ones involving the sciences and scholarship. It also provides intellectual tools to those who must assess potential violations of public or academic integrity. Many of these tools involve measurement mechanisms, ways of putting cases into context, and a recognition that few cases are simple black-and-white violations. Demonstrating that a binary approach to judging research integrity fails to recognize the complexity of the environment, Seadle highlights that even flawed discoveries may still contain value. Finally, the book reminds its reader that research integrity takes different forms in different disciplines and that each one needs separate consideration, even if the general principles remain the same for all. The Measurement of Information Integrity will help those who want to do research well, as well as those who must ascertain whether results have failed to meet the standards of the community. It will be of particular interest to researchers and students engaged in the study of library and information science"--
Introduction and approach -- Context and society -- Context and institutions -- Disciplines -- Measurement -- Actors -- Conclusion and consequences.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Information integrity; Information integrity -- Measurement